Practical strategies for enhancing gender equality and social inclusion in Innovation Platforms: Examples from agriculture and natural resource management - Elias, Marlène; Micheletti, Giulia (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Innovation Platforms (IPs) are multi-sectoral and multi-stakeholder ‘spaces’ that bring together actors with different interests in a specific area (e.g. an agricultural product value chain) to negotiate and develop innovations in a participatory manner (Schut et al. 2017). Their participatory nature is meant to ensure that agricultural innovations are not delivered to farmers in a top-down manner, but rather co-developed with farmers and other IP stakeholders. Yet, power asymmetries within IPs threaten the inclusive innovation processes IPs are meant to generate (Swaans et al. 2014). As inherently political spaces, IPs can thus inadvertently exacerbate existing power imbalances, or become hijacked by more powerful members and misused (Swaans et al. 2013). Skewed power relations occur not only vertically (across different types of stakeholder groups) but also horizontally, within communities. Richer farmers and businesspeople typically have more power than poorer community members, and can steer the conversation towards innovations that respond to their own strategic interests. Gender is an important factor shaping social dynamics in IPs. As gender norms attribute different roles, rights and responsibilities to women and men, women and men may favor different innovations, and have unequal capacities and opportunities to participate in IPs. Yet, gender is rarely discussed within the context of IPs. This omission limits the potential to understand processes of cooperation and inclusion in IPs (Swaans et al. 2013), and poses several risks to the success and equitability of the innovations IPs generate.